The Me Too Syndrome reloaded: Change and continuity in Italian relations with France and Germany after Brexit - Lorenzo Cladi; Andrea Locatelli (Italian Political Science, 2020)
The 2016 United Kingdom European Union membership referendum altered the European balance of power, leaving France and Germany as the only major powers in the EU. As a would-be peer within EU institutions, Italy was particularly exposed by this situation and adapted its foreign policy accordingly. Noting that Italy has displayed a mix of cooperation and conflict with France and Germany, our article seeks to answer why this has been the case. Focusing on the impact of party politics on foreign policy, we argue that Italian foreign policy resulted from the political synthesis developed by each of the Ital-ian cabinets ruling since 2016. The political synthesis depended, in turn, on the interplay between party ideology (pro- or anti-EU) and coalition dynamics. A cooperative foreign policy is then related to ideologically divided coalitions and those sharing a pro-EU ideology. On the contrary, an oppositional foreign policy depended on homogeneous, anti-EU coalitions.